Euthanasia of beached humpback whales using explosives - Coughran, Douglas K.; Stiles , Ian; Mawson , Peter R. (J. Cetacean Res. Manage., 2023)
A method for the safe and effective euthanasia of large beached humpback whales using explosives is described. Five recent case studies involving live stranded humpback whales measuring 9.1–12.7m are described to show how the method was applied, and the capacity of the method to deal with the varying conditions encountered when dealing with large baleen whales. Issues relating to the wider application of this method to other species of baleen whale and large odontocete species are discussed along with key safety implications for the safe use of this method.